Inflammation in Renal Diseases: New and Old Players - Andrade-Oliveira, Vinicius; Foresto-Neto, Orestes; Watanabe, Ingrid Kazue Mizuno; Zatz, Roberto; Câmara, Niels Olsen Saraiva (Frontiers in Pharmacology, 2019)
Renal inflammation, a common scenario in kidney diseases, is a complex network of interactions between renal parenchymal cells and resident immune cells, such as macrophages and dendritic cells, as well as recruitment of circulating cells, such as monocytes, lymphocytes and neutrophils. These immune cells once activated secrete several inflammatory mediators that can cause irreversible tissue damage, compromising organ function. Conversely, the crosstalk between kidney and other organs, such as the gut, may impact the course of these diseases. Several danger-associated molecules can be sensed by innate immune receptors and trigger renal inflammation through inflammasome-dependent and -independent pathways. This response leads to metabolic reprogramming and changes in phenotype and function of immune and parenchymal cells. Besides that, growing evidence suggests that changes in gut microbiota composition and/or its metabolites production exert positive regulatory effects on inflammation, oxidative stress and fibrosis, thus contributing to prevent the onset or development of renal diseases. Not by coincidence, attempts have been made to control inflammation in order to alleviate the renal damage. Here, we summarize the most recent data showing the potential of new approaches to treat inflammation in renal diseases such as probiotics, prebiotics and postbiotics administration. Moreover, we also mention here novel findings showing new target for known used drugs. Angiotensin II receptor antagonists, NF-κB inhibitors, thiazide diuretic and antimetabolic drugs reduce renal macrophage infiltration and slow down the disease progression. Allopurinol, an inhibitor of uric acid production, has been shown to decreased renal inflammation by limiting activation of the NLRP3 inflammasome. Increase of the arsenal of drugs to treat renal diseases and focus on microbiota, cellular metabolism and inflammation may lead to new therapeutical approaches aiming better control and prevention of the progression of renal diseases.